Characteristics of bone metabolism in postmenopausal women with newly diagnosed type 2 diabetes mellitus. (15th June 2021) - Li, Huijuan; Wen, Yuhua; Liu, Peipei; Zhang, Liya; Zhang, Xiaoya; Liu, Yichen; Ma, Bin; Kuang, Haidong; Wang, Jianxin; Song, Lige
Abstract: Objective: The characteristics of bone metabolism in T2DM are still controversial. This study aims to recognize bone turnover features in patients with newly diagnosed T2DM who have never been treated with anti‐diabetic drugs and further explore the possible factors contributing to their impaired bone turnover. Materials and Methods: An analytic sample of 88 patients with newly diagnosed T2DM and 152 non‐diabetic control individuals were studied. All the participants were postmenopausal women. Demographics variables and clinical history were recorded. We measured lipid profile, glucose metabolism, bone turnover markers indices as well as their related hormones, serum calcium and phosphorus. Bone mineral density was detected by dual‐energy X‐ray absorptiometry. We compared the differences in bone turnover markers and their regulating hormones between two groups and further analysed the factors related to bone turnover in T2DM. Results: Compared with the control group, patients with T2DM had a higher level of bone alkaline phosphatase (BALP), lower levels of procollagen type I intact N‐terminal (P1NP), osteocalcin (OC) and parathyroid hormone (PTH). Multiple linear regression analysis showed that in patients with T2DM, HbA1c was negatively correlated with P1NP and OC. For patients without diabetes, HbA1c was negatively related to BALP and OC. Conclusions: Patients with newly diagnosed T2DM may have impaired osteoblastic maturation and bone formation, which may be mainly attributed to hyperglycaemia.